Toluene degradation by Cupriavidus metallidurans CH34 in nitrate-reducing conditions and in Bioelectrochemical Systems. Issue 12 (16th May 2018) - Espinoza Tofalos, Anna; Daghio, Matteo; González, Myriam; Papacchini, Maddalena; Franzetti, Andrea; Seeger, Michael
Abstract: Bioelectrochemical remediation of hydrocarbons is a technology that exploits the ability of specific microorganisms to use as electron acceptor an electrode, thus potentially lowering the operational costs related to classical bioremediation. Several well-characterized hydrocarbonoclastic strains might be electroactive, thus their biodegradation performances in Bioelectrochemical Systems should be studied. Cupriavidus metallidurans CH34 is a model metal-resistant strain whose capacity to degrade benzene aerobically has recently been described. In this study, toluene degradation under anaerobic conditions and the exoelectrogenic capacity of Cupriavidus metallidurans CH34 were determined. Strain CH34 was grown anaerobically with toluene as sole carbon source in sealed serum bottles and then inoculated in a Microbial Electrolysis Cell (MEC) to assess its exoelectrogenic capacity. It was demonstrated for the first time that strain CH34 is able to degrade toluene under nitrate-reducing conditions (up to 45 mgtoluene /L were removed within 17 days, corresponding to 73% of toluene amended). Nitrate consumption and cellular growth were observed during toluene removal. In the MEC, toluene degradation was linked to current production, showing current peaks after every toluene addition (maximum current density 48 mA/m 2 ). Coulombic efficiency of the toluene biodegradation process increased with time, from 11% (first batch cycle), up to 77% (last batch cycle). Abstract : The need for new anode-respiring strains was approached and the exoelectrogenic capacity of Cupriavidus metallidurans CH34 during toluene degradation was assessed for the first time in this study.